GIS-Based Flood Risk Assessment Using the Analytical Hierarchy Process - Rakuasa, Heinrich; Rifai, Ahmat (PT. Teknologi Futuristik Indonesia, 2025)
Floods are a common hydrometeorological disaster in Teluk Ambon Sub-district ; therefore, modeling is necessary as a mitigation measure. To address this challenge, Geographic Information System (GIS) and Remote Sensing technologies have proven to be powerful tools in flood disaster analysis and modeling. This study uses 10 variables, including elevation, slope, TWI, NDVI, precipitation, land cover, soil type, drainage density, distance from roads, and distance from rivers. This study uses the Analytical Hierarchy Process (AHP) method. The results show that distance from rivers has the greatest contribution (14.08%) to flooding in Teluk Ambon Sub-district . The level of flood vulnerability in Teluk Ambon Sub-district is divided into three classes, namely low risk, covering an area of 8,642.26 ha or 64.71%; medium risk, covering an area of 4,066.79 ha or 30.45%; and high risk, covering an area of 646.44 ha or 4.84%. Settlements predicted to be affected by flooding in the low class cover an area of 130.36 ha, or 11.59%; the medium class covers an area of 649.29 ha, or 57.73%; and the high class covers an area of 345.07 ha, or 30.68%. The results of this study are very important in providing a more precise flood risk map to support spatial planning and disaster mitigation in the affected areas.